2019
DOI: 10.4049/jimmunol.1801346
|View full text |Cite
|
Sign up to set email alerts
|

Signals of the Neuropilin-1–MET Axis and Cues of Mechanical Force Exertion Converge to Elicit Inflammatory Activation in Coherent Endothelial Cells

Abstract: The neuropilin-1 (NRP1)-MET signaling axis regulates the motility of individual endothelial cells (ECs). It is unknown how this signaling pathway affects the endothelial barrier in coherent ECs forming a tight monolayer. We hypothesized that it is involved both in modulation of the endothelial barrier and in EC activation. To investigate the role of NRP1-MET signaling in inflammatory processes (e.g., systemic inflammatory response syndrome [SIRS] or snakebite-induced SIRS-like conditions), we employed the C-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…This elicits several pleiotropic effects in endothelial cells, among them the rearrangement of integrins and adhesomes, as well as of the adhesome-anchored actin cytoskeleton [151]. In a monolayer of coherent endothelial cells, rhodocetin-αβ induces their activation and consequently augments diapedesis of myeloid immune cells [201]. In two animal tumour models, this SV-CLRP does not primarily influence endothelial cells in normal vessels because of the inaccessibility of blood-borne rhodocetin-αβ to the basolaterally expressed neuropilin-1.…”
Section: Snake Venom-c-type Lectin-related Protein (Sv-clrps)/snacmentioning
confidence: 99%
“…This elicits several pleiotropic effects in endothelial cells, among them the rearrangement of integrins and adhesomes, as well as of the adhesome-anchored actin cytoskeleton [151]. In a monolayer of coherent endothelial cells, rhodocetin-αβ induces their activation and consequently augments diapedesis of myeloid immune cells [201]. In two animal tumour models, this SV-CLRP does not primarily influence endothelial cells in normal vessels because of the inaccessibility of blood-borne rhodocetin-αβ to the basolaterally expressed neuropilin-1.…”
Section: Snake Venom-c-type Lectin-related Protein (Sv-clrps)/snacmentioning
confidence: 99%
“… 24 Cerebral ischemia can lead to the activation of endothelial cells, which can accelerate the release of IL-6, TNF-α and other inflammatory factors. 25 Kamnaksh et al 26 have documented in their research that increased expression levels of IL-6 and TNF-α in the cerebrospinal fluid would indicate higher severity of the condition in patients with vascular cognitive impairment. Simultaneously, hippocampal gray matter volume is an important index to determine the severity of vascular cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…25 Cerebral ischemia can activate endothelial cells and accelerate the release of IL-6 and TNF-α. 26 Kamnaksh et al 27 showed that VCI worsened with the increase in IL-6 and TNF-α expression in cerebrospinal fluid; a higher plasma level of IL-6 indicated smaller hippocampal gray matter volume, a marker of severity in VCI patients. In other words, inflammatory responses probably affect the hippocampal gray matter via the IL-6 pathway.…”
Section: Discussionmentioning
confidence: 99%